Legal Protection of Refugee Rights: Challenges and Solutions - Brașoveanu, Florica (Technium Social Sciences Journal, 2023)
This paper focuses on the legal protection of refugee rights in a global context marked by forced migration and armed conflicts. Starting with an analysis of the evolution of the refugee concept and the development of relevant international regulations, the paper explores the legal status of refugees and the fundamental rights they possess under international law. The main rights examined include the right to asylum and non-refoulement, as well as the rights to life, liberty, and security, social and economic rights, rights of refugee children, and rights of refugee women. Additionally, the role of international agencies and non-governmental organizations in ensuring the legal protection of refugees is analyzed, along with the challenges and obstacles they face in practice. Finally, it proposes reforms and recommendations to enhance the legal protection of refugee rights with the aim of strengthening the effective application of international norms in this crucial area. This paper contributes to a comprehensive understanding of the legal protection of refugee rights and offers perspectives for a more efficient approach to this pivotal issue in the international community.